Justice for all Earl Warren and the nation he made - Newton, Jim (Riverhead Books, 2006)
Earl Warren played a key role in nearly every defining political moment in American history in the latter half of the twentieth century. He began as an aggressive county prosecutor offended by graft and vice, then rose through California politics. As attorney general and governor, he led the country's fastest-growing state during a time of enormous change, his support for the internment of Japanese Americans during World War II one of the few blemishes on an otherwise progressive record. From his historic governorship to his pivotal years as Chief Justice to his role as chairman of the commission that investigated the assassination of John F. Kennedy, Warren traversed the Depression and the Cold War, the struggles to defend America against foreign enemies, and the emergence of a muscular commitment to individual liberty.--From publisher description.